'Plus de figures!' On Saussure's use of images. (November 2016) - Christensen, Hans Dam
In this article, the spotlight is directed towards one of the supposed modern sinners contributing to the maintenance of the hierarchy between word and image, the Swiss linguist Ferdinand de Saussure (1857–1913) and in particular his chief work Cours de linguistique générale, published in 1916. Saussure was not explicit about the relation between word and image, but his work became a cornerstone in the development of modern linguistics and semiotics as well as later in the breakthrough of structuralism in the late 1950s and early 1960s. This article shows that Saussure was not as hostile to images that posterity seems to deduce from the more or less internalized 'verbocentrism' of large parts of semiotics and structuralism. Moreover, and most important, the article makes a contribution to a multifaceted understanding of signifying processes. First, the article presents the origin of Cours de linguistique générale ; almost simultaneously, another issue is introduced, namely the number of images in this work, which goes far beyond the few well-known illustrations. Secondly, these images are heuristically classified and, due to the origin of the book (primarily based on students' notes), the ownership and presence of these images are debated. Last, Saussure's semiotics is touched upon in light of the use of images in Cours de linguistique générale . The theoretical conclusions point to the fact that the making of knowledge is not embedded in language (or linguistics), but emerges in a play between several types of significations. In fact, as in everyday life and Saussure's lectures, communication is complex and the notion of abstracted sign systems ('language', etc.) from everyday communication is perhaps too reductive, as Saussure himself demonstrated by using images in his theory on linguistics as well as in his lectures.